2023
DOI: 10.1002/brb3.2932
|View full text |Cite
|
Sign up to set email alerts
|

White matter hyperintensities had a correlation with the cerebral perfusion level, but no correlation with the severity of large vessel stenosis in the anterior circulation

Abstract: Objective The contribution of large vessel stenosis to the development of white matter hyperintensities (WMHs) has not been fully elucidated. This study aims to explore the correlation between ipsilateral white matter hyperintensities (WMHs) and the severity of large vessel stenosis in the anterior circulation and cerebral perfusion level, as well as analyze the factors influencing WMHs. Methods A cross‐sectional study of 150 patients with unilateral anterior circulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…51,52 Recent studies also showed that asymmetry of cerebral perfusion due to LAD may give rise to a preferential increase in WMH and dilated periventricular space. [53][54][55] As discussed earlier, studies also showed an association between LAD and AD pathologies. LAD may also possibly have an etiological association with AD as the hypoperfusion related to the LAD or its obliteration of perforators can compromise the neurovascular units and BBB integrity, thus triggering amyloid/tau accumulation and the AD pathological cascades as well.…”
Section: Covert Brain Infarcts and Chronic Hypoperfusion Due To Large...mentioning
confidence: 58%
“…51,52 Recent studies also showed that asymmetry of cerebral perfusion due to LAD may give rise to a preferential increase in WMH and dilated periventricular space. [53][54][55] As discussed earlier, studies also showed an association between LAD and AD pathologies. LAD may also possibly have an etiological association with AD as the hypoperfusion related to the LAD or its obliteration of perforators can compromise the neurovascular units and BBB integrity, thus triggering amyloid/tau accumulation and the AD pathological cascades as well.…”
Section: Covert Brain Infarcts and Chronic Hypoperfusion Due To Large...mentioning
confidence: 58%
“…Our study was conducted to verify the correlation between ICAS and WMHs; however, the results were borderline. Several studies on ICAS and WMHs were excluded because of the lack of data available for meta-analysis, which reported contradictory results, including positive and null associations ( Chutinet et al, 2012 ; Li et al, 2014 ; Nam et al, 2017 ; Zhai et al, 2018 ; Zhao et al, 2019 ; Ren et al, 2021 ; Feng et al, 2023 ). The inconsistencies in the results might be due to the differences in study subjects, sample size, ICAS assessment method, WMHs rating method and statistical analysis between the studies.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial dysfunction (including cerebral blood flow, cerebrovascular reactivity, intracranial pulsatility) is a pivotal pathogenesis of cerebral small vessel disease ( Wardlaw et al, 2019 ). Three studies reported that WMHs were not directly related to arterial stenosis but were independently associated with the stenosis-induced cerebral hemodynamic changes in patients with ICAS ( Fang et al, 2020 ; Ren et al, 2021 ; Feng et al, 2023 ). Intracranial and extracranial atherosclerotic stenosis does not necessarily cause decreased cerebral blood flow ( Shakur et al, 2014 ) as it also depends on collateral blood flow, which may result in a null association between intracranial and extracranial atherosclerotic stenosis and WMHs in some previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, cerebral hypoperfusion has been associated with more severe WMHs in the general population and in patients with symptomatic ICAD (sICAD). 8,9 Moreover, thromboembolism and cerebral hypoperfusion have been associated with presence of CMIs. 10 These all need further investigations.…”
Section: Introductionmentioning
confidence: 99%